Deconstructing the Complexities of Racial Hierarchies: Representations of Black Identity and White Privilege in Harper Lee Literary Universe (International Journal of Scientific Research in Science and Technology, 2024)
This study delves into the intricate representations of racial hierarchies, specifically focusing on the depiction of Black identity and white privilege in Harper Lee’s literary universe. Through a critical examination of her works, particularly To Kill a Mockingbird and Go Set a Watchman, this analysis deconstructs the complexities of race relations, highlighting the pervasive influence of systemic racism and the deep-seated social structures that perpetuate racial inequality. Harper Lee’s portrayal of the American South provides a powerful critique of the racial dynamics that continue to shape the lives of individuals and communities, revealing the ways in which race, class, and power intersect to maintain social hierarchies. The study examines how Lee depicts the lived experiences of Black characters, contrasting these with the privileges enjoyed by white characters within the same societal framework. By exploring key themes such as the moral and legal disparities in the justice system, the social construction of race, and the psychological impact of racism on marginalized communities, this research seeks to uncover the layers of racial ideology embedded in Lee’s narrative. Moreover, the study investigates how Lee’s portrayal of white characters, particularly those in positions of power and influence, reflects the inherent privileges and unconscious biases that sustain racial hierarchies. The analysis also considers the role of white allies in the fight against racial injustice, evaluating the complexities and challenges they face in advocating for change within a racially stratified society.